Recombinant Expression and Phenotypic Screening of a Bioactive Cyclotide Against α‐Synuclein‐Induced Cytotoxicity in Baker′s Yeast1. (10th June 2015) - Jagadish, Krishnappa; Gould, Andrew; Borra, Radhika; Majumder, Subhabrata; Mushtaq, Zahid; Shekhtman, Alexander; Camarero, Julio A.
Abstract We report for the first time the recombinant expression of fully folded bioactive cyclotides inside live yeast cells by using intracellular protein trans‐splicing in combination with a highly efficient split‐intein. This approach was successfully used to produce the naturally occurring cyclotide MCoTI‐I and the engineered bioactive cyclotide MCoCP4. Cyclotide MCoCP4 was shown to reduce the toxicity of human α‐synuclein in live yeast cells. Cyclotide MCoCP4 was selected by phenotypic screening from cells transformed with a mixture of plasmids encoding MCoCP4 and inactive cyclotide MCoTI‐I in a ratio of 1:5×104. This demonstrates the potential for using yeast to perform phenotypic screening of genetically encoded cyclotide‐based libraries in eukaryotic cells.